FACTORS OF NATURE PROTECTION IN UZBEKISTAN DURING THE YEARS OF INDEPENDENCE - Badalbaeva Irodakhon Khabibulaevna; Adilova Umidakhan (American Journals Publishing, 2024)
This article discusses the factors of environmental protection in Uzbekistan during the years of independence: the further development of the activities of government bodies in the field of ecology and environmental protection, as well as the importance of protecting the natural environment, using natural resources and ensuring environmental safety.
Keywords: Nature conservation, natural environment, natural resources, Geographical Society of Uzbekistan, reserve, forestry, ecological culture, Action Strategy.